Correlation between aerobic training and physical endurance in basketball players - Ge, Z.; Lv, X.; Xue, Y. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: Endurance is a quality that has been lacking in Chinese athletes. In most endurance sports training in China, there is a problem with attaching importance to high-intensity anaerobic training and ignoring aerobic training. The close combination of aerobic, strength and technical training is endurance training. A significant development trend in training. Objective: This study analyzes the relationship between aerobic training and physical endurance in basketball players. Methods: Basketball players were selected and randomly divided into groups through the analysis method with a questionnaire, observation method, and experimental method to analyze the relationship between aerobic exercise and physical endurance in basketball players. In this paper, the changes in physiological indicators of basketball players were recorded after aerobic exercise. Results: The physical endurance of basketball players were positively correlated with aerobic training time. The physiological indicators of basketball players and basketball skills after aerobic training were significantly improved (P<0.05). Conclusion: Aerobic exercise can improve basketball players` physical endurance and overall physical fitness, helping them achieve good results in competitions.